Study Of The Correlation Between Solar Magnetic Reconnection Flux With Solar Flare Types And Duration - Kanniah, Balamuralikrishna (2022)
Solar flares are eruptive or confined electromagnetic radiation associated with a magnetic energy release in the solar atmosphere. To understand the characteristic, the linear correlation coefficient for total magnetic reconnection flux and flare duration versus flare class by flare type were find. The flare duration was derived from Geostationary Operational Environmental Satellites (GOES). The GOES X-ray sensors detect solar flare intensity and classify them as A, B, C, M, or X according to their peak fluxes. A total of 33 flare events of M5 to X5 flare classes within 45° of Sun’s disk center were examined, dated between February 2011 to September 2017. The flare is spotted using the AIA 1600 Å filtergram with a threshold of 1300 count. The magnetic flux was determined via the HMI 6173 Å filtergram. Their data are accessible through the Joint Science Operations Center (JSOC). Both images were co-registered and superimposed to identify the newly brightened pixels (AIA) then calculated the underlying magnetic field (HMI). The linear correlation between flare class against duration by Full Width Half Maximum (FWHM) is weak (0.19) before the segregation by flare types. However, the further breakdown shows confined flares have a higher linear correlations coefficient (0.58) than eruptive (0.08) no correlation.